2011
DOI: 10.1144/sp355.10
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic re-interpretation of the Banggai-Sula–Molucca Sea margin, Indonesia

Abstract: High resolution multibeam bathymetric and seismic data from the area north of the Banggai-Sula Islands, Indonesia, provide a new insight into the geological history of the boundary between the East Sulawesi ophiolite, the Banggai-Sula microcontinent and the Molucca Sea collision zone. Major continuous faults such as the Sula Thrust and the North Sula–Sorong Fault, previously interpreted to bound and pass through the area are not seen. The south-verging Batui Thrust previously interpreted offshore to the east o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…159, 173-174, 181-183;Silver et al, 1983]. Van Leeuwen et al [2010], Villeneuve et al [1998Villeneuve et al [ , 2000Villeneuve et al [ , 2001, and Watkinson et al [2011] date this collision as Pliocene. Davies [1990] showed that one block (Banggai) collided with the peninsula between 5.3 and 3.8 Ma, when clastic sedimentation on limestone began.…”
Section: A5 Sulawesi the Makassar Strait And The Sula Islandsmentioning
confidence: 99%
“…159, 173-174, 181-183;Silver et al, 1983]. Van Leeuwen et al [2010], Villeneuve et al [1998Villeneuve et al [ , 2000Villeneuve et al [ , 2001, and Watkinson et al [2011] date this collision as Pliocene. Davies [1990] showed that one block (Banggai) collided with the peninsula between 5.3 and 3.8 Ma, when clastic sedimentation on limestone began.…”
Section: A5 Sulawesi the Makassar Strait And The Sula Islandsmentioning
confidence: 99%
“…The dip of local crustal faults was sourced from published estimates obtained from seismic reflection data (Rigg and Hall, 2012;Watkinson et al, 2011Watkinson et al, , 2012 and from the global CMT catalogue (Ekstrom et al, 2012). For the Sunda Arc, the fault geometry used by the InaTEWS was adopted to allow compatibility between the two tsunami databases Strunz et al, 2011).…”
Section: Local Sourcesmentioning
confidence: 99%
“…Sediments from the colliding wedges are being extruded to the south (Silver & Moore, 1978;Moore & Silver, 1983) and show a chaotic structure indicative of continuous deformation distributed across many small faults and folds rather than localised on large crustal structures (Watkinson et al, 2011). Tsunamigenic earthquakes are likely to happen here too.…”
Section: Molucca Sea (Sangihe Thrust Sangihe Backthrust and Halmahermentioning
confidence: 99%